2016
DOI: 10.1002/1873-3468.12276
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a Trypanosoma cruzi glucose‐6‐phosphate dehydrogenase reveals differences from the mammalian enzyme

Abstract: Edited by Richard CogdellThe enzyme glucose-6-phosphate dehydrogenase from Trypanosoma cruzi (TcG6PDH) catalyses the first step of the pentose phosphate pathway (PPP) and is considered a promising target for the discovery of a new drug against Chagas diseases. In the present work, we describe the crystal structure of TcG6PDH obtained in a ternary complex with the substrate b-D-glucose-6-phosphate (G6P) and the reduced 'catalytic' cofactor NADPH, which reveals the molecular basis of substrate and cofactor recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…Finally, we report the first 3D structural model of the G6PD domain of the G6PD::6PGL from G. lamblia , with important differences compared to the human G6PD enzyme. These structural dissimilarities with respect to human G6PD make the G6PD::6PGL from G. lamblia an ideal target for drug development, as the same approach has been used successfully in other parasites such as P. falciparum and Trypanosoma cruzy [ 14 , 26 , 41 ]. In P. falciparum , the 3D structure of PfG6PD‒6PGL compared to the human enzyme (G6PD) was reported, where a key difference in the substrate-binding site was shown that involves the replacement of Arg365 in human by Asp750 in PfG6PD.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we report the first 3D structural model of the G6PD domain of the G6PD::6PGL from G. lamblia , with important differences compared to the human G6PD enzyme. These structural dissimilarities with respect to human G6PD make the G6PD::6PGL from G. lamblia an ideal target for drug development, as the same approach has been used successfully in other parasites such as P. falciparum and Trypanosoma cruzy [ 14 , 26 , 41 ]. In P. falciparum , the 3D structure of PfG6PD‒6PGL compared to the human enzyme (G6PD) was reported, where a key difference in the substrate-binding site was shown that involves the replacement of Arg365 in human by Asp750 in PfG6PD.…”
Section: Resultsmentioning
confidence: 99%
“…Mercaldi et al (52) reported that this G6PDH displays a key amino acid residue in the 2-2 domain, R72, which specifically interacts with the 2-phosphate group of NADPH (Fig. 6A).…”
Section: Resultsmentioning
confidence: 97%
“…One elegant example in this direction is the analysis of the (unique) G6PDH enzyme of the parasitic euglenoid Trypanosoma cruzi (51). Mercaldi et al (52) reported that this G6PDH displays a key amino acid residue in the β2-α2 domain, R72, which specifically interacts with the 2′-phosphate group of NADPH (Fig. 6A) .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…T. brucei and L. mexicana have a single copy sequence, whereas T. cruzi has five copies, two of them being pseudogenes. The crystal structure of the TcG6PDH revealing the molecular basis of substrate and cofactor recognition was recently obtained showing that differences in the cofactor binding site compared to the human homologue allowing future exploration towards the design of new competitive NADP+ inhibitors [250].…”
Section: Oxidative Branchmentioning
confidence: 99%